2011
DOI: 10.1007/s00276-011-0888-5
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical anatomy of distal medial striate artery (recurrent artery of Heubner)

Abstract: Iatrogenic damage or occlusion leads to a mediobasal striatum infarction with important neurological deficits such as brachiofacial hemiparesis and aphasia. This artery should be routinely identified during clipping of ACoA aneurysm. Special attention in this study was given to atypical posterior course or anatomic variations such as double DMSA on a same side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…The microsurgical report of Zunon-Kipré et al concluded that A2 is the most common origin of RAH (58% of cases). The RAHs were more often originated from A1, in 30% of cases, than at the ACA-ACoA junction, in 12% of cases [3]. Similar conclusion was shown in the study of Perlmutter and Rhoton on 50 adult brains.…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…The microsurgical report of Zunon-Kipré et al concluded that A2 is the most common origin of RAH (58% of cases). The RAHs were more often originated from A1, in 30% of cases, than at the ACA-ACoA junction, in 12% of cases [3]. Similar conclusion was shown in the study of Perlmutter and Rhoton on 50 adult brains.…”
Section: Discussionsupporting
confidence: 72%
“…The different organization of these channels can be the result of the variable origin, number, size, or course of the artery. The RAH is a branch from the primitive olfactory artery as the ophthalmic artery, the anterior choroid artery, and the MCA [3]. The artery is well developed at the twenty-fourth week of gestation [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations